Translation of names of figures in the “Mushaf Brunei Darussalam dan Terjemahannya” - Salwani Sabtu,; Syed Nurulakla Syed Abdullah,; Salina Husain,; Ilyana Jalaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article revolves around the translation of names of figures in the Quran into the Malay language in the “Mushaf Brunei Darussalam dan Terjemahannya” (MBDT). It attempts at investigating the strategies for translating the names of the figures, namely the Prophets, their family members, companions, enemies, and other significant individuals in the history of the Prophets. The strategies are examined in terms of their effectiveness and appropriateness in producing successful translations for the names that could be well-comprehended by the target readers. As these names are of Arabic origin and culture-related, translators are therefore liable to confusion or mistakes when translating them into other languages, as can be seen in some English translations of the Quran. Translating the names into Malay is no exception and poses different translation challenges as Malay and Arabic belong to distant and different language families and cultures. The research method employed was the qualitative approach by textual analysis. The data were first collected from all the chapters in the Quran, and then from their Malay equivalents in the MBDT. The data were then compared and analysed descriptively, based on the Fernandes’ taxonomy for translating proper names (2006). The findings of the study showed that the translators of the MBDT incorporated either only one strategy or a combination of two or three strategies in conveying the names of figures into Malay with “transcription” being the most preferred strategy. Therefore, translators have to be wise in resolving the issues arising from the complexity of certain proper names.